Small business growth: strategic goals and owner preparedness - Weber, Paull; Geneste, Louis; Connell, Julia (Emerald Group Publishing Limited, 2015)
Purpose: This paper aims to identify and empirically test whether growth preparedness and success perceptions are important, discriminating small business owner (SBO) characteristics that influence strategic direction. The intended outcome was to create a strategic typology that resonates with the realities of small business owners, their advisors and policy makers. Design/methodology/approach: Empirical data were collected online and by postal survey from 340 small businesses from multiple industry sectors across Australia. Analysis is correlational resulting in the development of a 2 × 2 matrix of strategy types. Findings: This paper provides evidence that although a majority of SBOs are not preparing for growth, many still perceive their business as successful. Further, the empirical data demonstrate that growth preparedness and perceived success can be used to classify SBOs into distinct strategic types. While the categories developed show some similarities with the Miles and Snow (1978) typology, they also highlight divergent qualities. Consequently, this paper identifies circumstances where small business strategy must be treated differently from the larger enterprises for which the Miles and Snow typology was developed. Practical implications: By providing a concise tool for inclusion in surveys, researchers and practitioners can identify varying strategic types within their own targeted business cohorts. Originality/value: The growth/success matrix is original, the value for policy makers and other professionals assisting and supporting SBOs lies in its simplicity as a tool for identifying strategic types in any small business population. Specifically, the matrix provides a valid and reliable empirical analysis tool where none previously existed.